Effect of Nb-doping on electrical properties of Pb(Zr0.52Ti 0.48)O3 ceramics - P. Ketsuwan (2018)
In this study, electrical properties of Nb-doped Pb(Zr 0.52Ti0.48)O3 ceramics were investigated as function of sintering temperature and Nb concentration. First, effects of sintering temperature on physical and electrical properties of the Pb(Zr 0.52Ti0.48)O3 ceramics with addition of lwt% Nb2O5 prepared by conventional mixed oxide technique were investigated. The samples were sintered over temperature rang 1200-1300 °C. The dielectric constant increased with increasing sintering temperature from 1200 to 1250 °C. Further increase in temperature resulted in a drop of the dielectric constant. Similar trend was also observed for the d 33-constant. For the ferroelectric properties, the electrical coercivity and remnant polarization decreased with increasing sintering temperature, especially the optimum soft piezoelectric behavior with high εr, d33 and low Ec is observed in ceramics sintered at 1250 °C. Effect of Nb concentration varying between 0.75 and 1.50 %wt was also investigated at fixed sintering temperature of 1250 °C. It was found that the average grain size of the ceramics tended to decrease with increasing Nb concentration. The room temperature dielectric constant and d 33 reached maximum value at 1 %wt Nb-doping The electrical coercivity(Ec) of Nb-doped PZT increased with increasing Nb concentration, while the polarization values was independent of the Nb concentration. Copyright © 2007 MS&T'07®.